Magma Source Evolution Following Subduction Initiation: Evidence From the Element Concentrations, Stable Isotope Ratios, and Water Contents of Volcanic Glasses From the Bonin Forearc (IODP Expedition 352) - Daniel A. Coulthard Jr; Mark K. Reagan; Kenji Shimizu; Ilya N. Bindeman; Maryjo Brounce; Renat R. Almeev; Jeffrey Ryan; Timothy Chapman; John Shervais; Julian A. Pearce (Geochemistry, Geophysics, Geosystems, 2021)
Abstract International Ocean Discovery Program Expedition 352 to the Bonin forearc drilled the sequence of volcanic rocks erupted in the immediate aftermath of subduction initiation along the western margin of the Pacific Plate. Pristine volcanic glasses collected during this expedition were analyzed for major and trace elements, halogens, sulfur, and H and O isotopes with goals of characterizing the fluids and melts of subducted materials that were involved in generating the nascent upper plate crust. Incompatible trace element compositions of the oldest lavas (forearc basalts [FAB]) are similar to those of the most depleted mid‐ocean ridge basalts globally. Most FAB were generated by decompression melting during seafloor spreading in a near‐trench, supra‐subduction zone environment with only minor involvement of diverse and generally dilute water‐rich fluids from the subducting plate. Boninite series glasses are enriched in incompatible trace elements mobilized from the subducting plate, but strongly depleted in other elements, such as the middle‐heavy rare‐earth elements. These traits are attributed to generation of boninites largely by flux melting involving water‐rich melts first derived from the leading edge of subducted basaltic crust and then from both subducted crust and sediment. These melts were generated at low pressures as the shallow, embryonic slab extracted heat from hot asthenosphere near the trench. The progressive depletion of the mantle source for the FAB‐through‐boninite sequence suggests that the asthenospheric mantle remained trapped above the nascent subducting plate for the first several million years of subduction beneath the Philippine Sea Plate.